A Paradigm Shift of English Lecturers to Support Education Technology in Online Learning - Margaret Stevani; Karisma Erikson Tarigan (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The critical ability of English lecturers to education technology 4.0 could change the role of the traditional English lecturer because there needed to be a balance between soft skills and technological competencies. The value of digital transformation had shown that pedagogical interventions with student-centered pedagogy could design learning support goals and strategies and critically evaluate English lecturers’ self-management as professional trainers. The objectives of this study were to examine: (1) the role and innovation of English lecturers in the face of the paradigm shift in online learning, and (2) the conditions of digital learning related to lecturers` competencies. Focusing on qualitative data collected from 23 English lecturers at some higher education institutions in Indonesia, the results of English lecturer responses showed that the lecturers’ digital skills enhanced the following factors, such as knowledge, the students’ responsiveness to tasks, contextualized teaching and learning, and the stimulating of ideas as feedback thereby assisting the universities in recognizing the value of technology as their teaching needs. The data responses could reflect how the lecturers transformed learning through innovative pedagogical concepts and the use of digital in the classroom. Future research could strengthen the pedagogical profile for education 4.0 to master technology with a global view of world culture.